2017
DOI: 10.1016/j.jegh.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of OMNIgene·SPUTUM performance in delayed tuberculosis testing by smear, culture, and Xpert MTB/RIF assays in Uganda

Abstract: OMNIgene·SPUTUM (OM-S) is a sample transport reagent designed to work with all tuberculosis diagnostics while eliminating the need for cold chain. OM-S-treated sputum samples were assayed in several tests after multiday holds. Raw sputa from 100 patients underwent direct smear microscopy, were manually split and assigned to the OM-S group [OM-S added at collection (no other processing required) and tested after 0- to 5-day holds at room temperature] or standard-of-care (SOC) group (NaOH/N-acetyl l-cysteine dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
3
13
2
1
Order By: Relevance
“…In addition, we have shown that OM-S-treated MGIT samples had longer TTP: 4 and 10 days longer in same-day and 5-day samples, respectively. The effective suppression of contaminants and the longer TTP concur with previous evaluation studies of OM-S [ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, we have shown that OM-S-treated MGIT samples had longer TTP: 4 and 10 days longer in same-day and 5-day samples, respectively. The effective suppression of contaminants and the longer TTP concur with previous evaluation studies of OM-S [ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…Unlike PrimeStore transport medium, which eliminates viability by killing M. tuberculosis and is only suitable for downstream molecular assays, OM-S maintains viability important for culture and culture-based DST [ 14 ]. Previous evaluation reports demonstrate compatibility of OM-S-treated samples with using Lowenstein Jensen (LJ), MGIT and Xpert, with TB detection results comparable to standard of care in these tests [ 7 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the cell wall represents a challenge to the organism, 10 requiring specialized mechanisms to allow cell division to occur and resulting in prolonged 11 generation times compared to gram-positive or -negative bacteria. 4 Respiratory samples are 12 therefore specially treated, a process called 'decontamination' before inoculation and incubation 13 of broth and solid media. Decontamination and the supplementation of broth and media with 14 antibiotics and antifungals are intended to prevent overgrowth of the slower growing 15 mycobacteria by concomitant flora of specimens from non-sterile sites.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with the findings from other studies reporting lower 174 culture contamination rates when using OMNIgene ® SPUTUM reagent. 12,16 The difference 175 might be explained by differences in patient populations. The majority of patients submitting 176 sputum samples for this study were on treatment for drug susceptible or resistant tuberculosis 177 and hence contamination rates were particularly high.…”
mentioning
confidence: 99%
“…OM-S has the ability to liquefy and decontaminate samples at the same time, offering the possibility to extend their storage until 8 days at temperatures up to 40°C prior to culture inoculation (8). However, studies investigating the effect of OM-S have shown good accuracy but mainly with Lowenstein-Jensen (LJ) culture (10,11), while those using MGIT have reported contrasting results (12)(13)(14)(15).…”
mentioning
confidence: 99%